2013
DOI: 10.1177/0309364612463164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of powered gait orthosis on walking in individuals with paraplegia

Abstract: Background: The important purpose of a powered gait orthosis is to provide active joint movement for patients with spinal cord injury. Objectives: The aim of this study was to clarify the effect of a powered gait orthosis on the kinematics and temporalspatial parameters in paraplegics with spinal cord injury. Study Design: Quasi-experimental. Methods: Four spinal cord injury individuals experienced gait training with a powered gait orthosis for a minimum of 6 weeks prior to participating in the following walki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Twelve studies evaluated the effects of different hip joint options on walking parameters and energy expenditure. 5,[12][13][14][15][16][17][18][19][20][21][22] These studies had low level of evidence according to the PEDro score (2/10). Table 3 provides details on the studies evaluating modified hip joints in patients with SCI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies evaluated the effects of different hip joint options on walking parameters and energy expenditure. 5,[12][13][14][15][16][17][18][19][20][21][22] These studies had low level of evidence according to the PEDro score (2/10). Table 3 provides details on the studies evaluating modified hip joints in patients with SCI.…”
Section: Resultsmentioning
confidence: 99%
“…The means of speed of walking were reported 0.17, 0.19, 0.22, 0.25 and 0.34 m per second. 14,15,20,62,63 The mean of energy consumption was reported 120 ± 6 to 140 ± 11 beats per min) 144 beats per min. 14,62 In the modified hip joint category in using MLO, the values of this parameter were reported 0.11, 0.14, 0.33 m per second with WO, 16,26 0.13 with Moorong, 0.6 m per second with HALO 16,18 and 0.39 with new reciprocating MLO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effect of orthoses on walking in SCI patients has been reported, 22,[42][43][44] few publications have analysed the efficacy of PO compared with mechanical orthoses on energy expenditure in SCI subjects. PO were designed with the concept of providing active lowerextremity motion for SCI patient ambulation, especially those who are unable to swing their leg voluntarily, 45,46 and it has been demonstrated that temporal spatial parameters of walking can be improved with this type of orthosis compared with mechanical orthoses by providing active joint motions.…”
Section: Discussionmentioning
confidence: 99%
“…10 In a comparison of different types of RGO in providing adequate walking speed by SCI patients, it has been reported that IRGO provides the highest speed. 1 Arazpour et al 17 reported a gait speed of 0.4 m s − 1 after 6 weeks of gait training with a powered gait orthosis in four SCI patients.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%